2014
DOI: 10.1002/ange.201409293
|View full text |Cite
|
Sign up to set email alerts
|

Ring‐Opening Polymerization of Prodrugs: A Versatile Approach to Prepare Well‐Defined Drug‐Loaded Nanoparticles

Abstract: We report a new methodology for the synthesis of polymer-drug conjugates from "compound"-all in one-prodrug monomers that consist of a cyclic polymerizable group that is appended to a drug through a cleavable linker. We show that organocatalyzed ring-opening polymerization can polymerize these monomers into well-defined polymer prodrugs that are designed to self-assemble into nanoparticles and release drug in response to a physiologically relevant stimulus. This method is compatible with structurally diverse d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 43 publications
(7 reference statements)
0
35
0
Order By: Relevance
“…The “conjugation through” method could address the drawbacks in the “conjugation to” strategy, such as inconsistent and uncontrolled site conjugation along the polymer backbone . The drug loading can be controlled by adjusting the feed ratio of monomer‐drug conjugates; and the drug release can be controlled by the judicious selection of the linker between the drug and the monomer, which could be stimulus‐responsive (Figure b) . Such method thus allows for even higher drug‐loadings than the “conjugation to” approach, by avoiding steric hindrance and accessibility limitation during the conjugation.…”
Section: New Strategies In Pdcmentioning
confidence: 99%
See 2 more Smart Citations
“…The “conjugation through” method could address the drawbacks in the “conjugation to” strategy, such as inconsistent and uncontrolled site conjugation along the polymer backbone . The drug loading can be controlled by adjusting the feed ratio of monomer‐drug conjugates; and the drug release can be controlled by the judicious selection of the linker between the drug and the monomer, which could be stimulus‐responsive (Figure b) . Such method thus allows for even higher drug‐loadings than the “conjugation to” approach, by avoiding steric hindrance and accessibility limitation during the conjugation.…”
Section: New Strategies In Pdcmentioning
confidence: 99%
“…Similarly, the reversible addition fragmentation transfer (RAFT) polymerization is reported for “conjugation through” method; for example, Cpt‐tethered acrylate with redox‐sensitive disulfide linker was polymerized by RAFT to formulate redox‐sensitive NPs . However, PDCs synthesized by the ROMP or RAFT had non‐biodegradable polymer backbones, which limits their potential clinical application . Alternatively, the ring‐opening polymerization (ROP) is applied in “conjugation through” method.…”
Section: New Strategies In Pdcmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this popular strategy may suffer from some potential drawbacks, such as low yield due to multi-step reactions involved, limited control of the conjugation sites, and relatively low drug loading [139141]. To overcome these limitations, direct polymerization of polymerizable drugs has been pursued.…”
Section: Molecular Building Blocks For One-component Nanomedicinementioning
confidence: 99%
“…Their in vitro and in vivo results suggested that the staggered lamellae are superior to the other three nanostructures. Very recently, Chilkoti and co-workers used the ring-opening polymerization to homo or hetero-polymerize both CPT and chlorambucil (CL) prodrugs, initiated by a PEG macroinitiator [139]. These amphiphilic diblock copolymers can spontaneously self-assemble into nanoparticles, where drugs are sequestered in the core that is coated with a PEG corona.…”
Section: Molecular Building Blocks For One-component Nanomedicinementioning
confidence: 99%